Fan assisted extraction and HPLC-DAD-MS/MS identification of volatile carbonyl compounds as chemical descriptors of healthy and defective roasted coffee beans. (August 2022) - Teixeira, Sandra Lopes; Santos, João Rodrigo; Almeida, P.J.; Rodrigues, J.A.
Abstract: In this work, the profile of the volatile carbonyl compounds in roasted coffee is performed. The assays focussed healthy coffee beans and the main typologies of defective beans (black, immature, sour and bored) of arabica and robusta species, roasted at light, medium and dark intensities. To perform the volatile compounds extraction, a fan-assisted extraction system was used. The experimental parameters temperature, sample treatment, sample mass and extraction period were evaluated. An efficient extraction of the volatile compounds could be accomplished after a 10 min period (RSD <10%). Twenty volatile carbonyl compounds were identified. Hexanal signal was of high intensity in roasted black beans. Butanal and 2-methylbutanal signals presented high intensity in sour and black robusta beans. Several compounds were of higher prevalence in healthy beans than in defective beans. Among them, furfural was considered the main indicator of healthy beans based on the highest signal difference observed between healthy and defective beans in arabica and robusta coffees at light, medium and dark roast degree. Highlights: Fan assisted extraction system to enhance volatile compounds' extraction. Profiling of volatile carbonyl compounds of roasted defective coffee beans. Butanal and 2-methylbutanal in higher amounts in sour and black robusta beans. Hexanal signal of higher intensity in black coffee beans. 2-Methyloxolan-3-one and furfural as indicator compounds of healthy coffee beans.